Extreme Magnetosphere‐Ionosphere‐Thermosphere Responses to the 5 April 2010 Supersubstorm. Issue 4 (14th April 2020) - Nishimura, Y.; Lyons, L. R.; Gabrielse, C.; Sivadas, N.; Donovan, E. F.; Varney, R. H.; Angelopoulos, V.; Weygand, J. M.; Conde, M. G.; Zhang, S. R.
Abstract: The extreme substorm event on 5 April 2010 ( THEMIS AL = −2, 700 nT, called supersubstorm) was investigated to examine its driving processes, the aurora current system responsible for the supersubstorm, and the magnetosphere‐ionosphere‐thermosphere (M‐I‐T) responses. An interplanetary shock created shock aurora, but the shock was not a direct driver of the supersubstorm onset. Instead, the shock with a large southward IMF strengthened the growth phase with substantially larger ionosphere currents, more rapid equatorward motion of the auroral oval, larger ionosphere conductance, and more elevated magnetotail pressure than those for the growth phase of classical substorms. The auroral brightening at the supersubstorm onset was small, but the expansion phase had multistep enhancements of unusually large auroral brightenings and electrojets. The largest activity was an extremely large poleward boundary intensification (PBI) and subsequent auroral streamer, which started 20 min after the substorm auroral onset during a steady southward IMF B z and elevated dynamic pressure. Those were associated with a substorm current wedge (SCW), plasma sheet flow, relativistic particle injection and precipitation down to the D‐region, total electron content (TEC), conductance, and neutral wind in the thermosphere, all of which were unusually large compared to classical substorms. The SCW did not extend over the entire nightside auroral activity but was localized azimuthally to a few 100 km in the ionosphere around the PBI and streamer. These results reveal the importance of localized magnetotail reconnection for releasing large energy accumulation that can affect geosynchronous satellites and produce the extreme M‐I‐T responses. Plain Language Summary: Supersubstorms are extreme space weather events that involve unusually intense aurora. The goal of this study is to understand the driving processes and system responses during a supersubstorm event on 5 April 2010, when the Intelsat Galaxy‐15 experienced an anomaly and stopped responding to ground commands. We found that the supersubstorm was associated with a particular type of aurora called poleward boundary intensification and a subsequent auroral streamer. This type of aurora can often occur, but the one in this event was unusually large ( AL = −2, 700 nT), in association with extremely intense currents and relativistic particle acceleration. The accelerated particles precipitated down to 60 km altitude, much lower than the typical height of aurora (>100 km). This event was caused by extremely intense magnetic reconnection and fast flows toward the Earth. This event also created a fast stream of neutral species in the upper atmosphere. Key Points: The supersubstorm is characterized by unusually large expansion‐phase auroral brightenings, including a PBI and auroral streamer The supersubstorm also had an intense SCW, plasma flow, particle injection and precipitation, TEC, conductance and wind Extreme responses were caused by unusually large energy accumulation and release by localized tail reconnection and particle acceleration